ALINE/LALINET Network Status - Landulfo, Eduardo (2016)
The Latin American Lidar Network, ALINE a.k.a LALINET is a federation lidar network established in 2008 which became a member of GALION/GAW program in 2013. Currently the network consists of 9 operational stations with the perspective of two more stations to be included. The network today covers more than 18 million Km2 and spans in latitude from -52o to 21o and in longitude from -78o to -47o . It should cover a larger area in the future as planned with the inclusion of more active stations